2019
DOI: 10.1177/2381468319892572
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Primary Care Clinician Communication About Risk, Benefits, and Goals Related to Chronic Opioid Therapy

Abstract: Background. Safe opioid prescribing and effective pain care are particularly important issues in the United States, where decades of widespread opioid prescribing have contributed to high rates of opioid use disorder. Because of the importance of clinician-patient communication in effective pain care and recent initiatives to curb rising opioid overdose deaths, this study sought to understand how clinicians and patients communicate about the risks, benefits, and goals of opioid therapy during primary care visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In response, patients requested additional information about risks or contributed their own information or understanding to the risk discussion. 12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, patients requested additional information about risks or contributed their own information or understanding to the risk discussion. 12 …”
Section: Resultsmentioning
confidence: 99%
“… 14 Another study suggested describing the patient's opioid use in the context of current guidelines or institutional policies and non-opioid treatment options for chronic pain as a tool to support decisions regarding opioid tapering. 12 …”
Section: Resultsmentioning
confidence: 99%
“…EPIS describes four phases of implementation for evidence-based interventions and the factors that influence the implementation process and outcomes [ 34 , 35 ]. The “Exploration” phase begins when stakeholders become aware of a public health or clinical need and thus includes our team’s prior work [ 27 , 28 , 36 42 ], prior interoperable CDS development for chronic pain [ 31 , 43 ], and the development of this protocol. The “Preparation” phase objectives are to identify barriers and facilitators to implementation, assess need for adaptation, and develop an implementation plan.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative reactions produce reactive oxygen species (ROS), reactive nitrogen species, reactive carbonyl species, and metal-free radicals. Antioxidant mechanisms are classified as enzymatic (superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx)) or nonenzymatic (vitamin C, vitamin E, glutathione (GSH), thioredoxin system, lipoic acid, carotenoids, and flavonoids), and these control the formation and elimination of free radicals [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%